Financial Development and Growth in the Middle East and North Africa - Creane, Susan (Pamphlet Series; Pamphlet Series, No., 2003)
In this study, the authors assess financial sector development in the MENA regionand propose several policy measures, which include reinforcing the institutional environment and promoting nonbank financial sector development, to enhance this sector's performance.